Answer:
y = 2x - 6
n = 22
Explanations:
By careful observation of the data in the table, the table has a constant rate of change, that is, a constant slope, hence it represents a staight line
The slope is calculated using the formula:
![m\text{ = }(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/sukh4lu5s7fgiz5v423o6usjd9gul4kfrj.png)
In the table:
x₁ = 8, y₁ = 10, x₂ = 9, y₂ = 12
![\begin{gathered} m\text{ = }(12-10)/(9-8) \\ m\text{ = }(2)/(1) \\ m\text{ =2 } \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/oaluid64lei3m8itr3uyq98cukn3q4hdfl.png)
Since we have confirmed that the table shows a linear equation, the equation of a line shown below can be used to form the relationship
![y-y_1=m(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/csobd57zth7rh9k4hz9amldzpq2owf0z4j.png)
![\begin{gathered} y\text{ - 10 = 2(x - 8)} \\ y\text{ - 10 = 2x - 16} \\ y\text{ = 2x - 16 + 10} \\ y\text{ = 2x - 6} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ne0czq6qpxj2ti3con42wku2vrom6m1e98.png)
The rule is therefore y = 2x - 6
To find the variable n, substitute y = n, and x = 14 into the equation y = 2x - 6
n = 2(14) - 6
n = 28 - 6
n = 22